Brain Derived Neurotrophic Factor (BDNF) As a Predictive Biomarker of the Occurrence of Post Traumatic Stress Disorder (PTSD) - H. Belhadj-Tahar; N. Sadeg (Highlights on Medicine and Medical Science Vol. 1, 2021)
The primary goal of the pilot study was to determine the rate of serum BDNF and the initial clinical course of a subject who had been exposed to a potentially traumatic incident over the course of three months. In this study 12 volunteers were recruited, 7 have been exposed to a traumatic event and 5 negative controls without psycho-trauma history. In this study, there is no correlation between circulating levels of cortisol and BDNF. The following are the findings of this study: In comparison to the control group, the rate of BDNF was substantially lower in the trauma group of volunteers: 6.20±1.73 ng / ml for the group with trauma versus 21.79±1.76 ng / ml for the control group with p<0.001. When compared to those who have experienced a traumatic event, the rate of serum BDNF is substantially reduced in victims of physical aggression: 4.36±0.37 ng / ml Assault group versus 6.94±1.44 ng / ml control group event with p = 0.03. The level of BDNF is significantly inversely correlated with the intensity of the Peritraumatic distress (r = -0.75, p <0.05). When compared to the group without PTSD, the rate of serum BDNF was significantly lower in the group with acute PTSD: 7.5±0.9 ng / ml in the absence of PTSD (n = 4) versus 4.5 ±0.4 in the presence of PTSD (n = 3), p = 0.001.